Antecedents of visitors' responsible behaviour and willingness to conserve in Borobudur Temple, Indonesia - Fibayani, Alifah Faidurrohmah (2022)
Borobudur Temple is one of the World Heritage Sites in Indonesia categorised under cultural heritage sites by UNESCO. The Temple faces several issues regarding the over-visitation during the public holiday that reaches more than 50,000 visitors a day, while the carrying capacity of the temple is only 123 people at a time. Another issue faced by Borobudur Temple is the high visitors’ irresponsible behaviour in the temple that damaged the temple stones. Therefore, the purpose of this study is to examine he antecedent of visitors’ responsible behaviour in Borobudur Temple and its relationship with their willingness to conserve the heritage site. A self-administered survey was conducted to visitors of Borobudur Temple between 17 January 2020 to 21 January 2020, followed by an online survey until May 2020 due to the Covid-19 pandemic in Indonesia. In total, 360 respondents participated in the survey, which consisted of 306 Indonesian visitors and 54 international visitors selected using the purposive sampling method. The collected data was analysed using Structural Equation Modelling (SEM) in Partial Least Square (PLS) program. The findings of this study reveal that visitors’ environmental knowledge, types of visitors, place attachment, and preferred management actions directly affect visitors’ responsible behaviour in Borobudur Temple. Place attachment also mediates the relationship between visitors’ environmental knowledge, psychological ownership, types of visitors, and visitors’ responsible behaviour. Additionally, visitors’ responsible behaviour directly affects visitors’ willingness to conserve Borobudur Temple. These findings provide significant implications for the scientific and practical field in maintaining Borobudur Temple sustainability, especially in understanding the factors that affect visitors’ responsible behaviour and preferred management actions in Borobudur Temple. Therefore, Borobudur Temple management could prepare a better plan to improve visitors’ responsible behaviour and willingness to conserve Borobudur Temple.